2014
DOI: 10.4238/2014.june.18.8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness between Ardi, Black Bedouin and Damascus goat breeds

Abstract: ABSTRACT.The present study aimed to analyze genetic relatedness and differentiation of common native goat populations in some countries of the Middle East. The populations were Ardi, Black Bedouin, and Damascus goats in the Kingdom of Saudi Arabia, Jordan, and Syria, respectively. Domesticated goats of the Middle East are mostly related to common ancestors, but there is limited molecular genetic evidence. Four microsatellite DNA markers were genotyped in 89 individuals of the three populations using an automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These potential incidences of gene flow were expecting in the closer regions of the tropics. Similar results were reported for goats of geographically close countries (Cañón et al, 2006;Al-Atiyat and Aljumaah, 2014). Considering different species, similar observations of reshaping genetic structure by genetic network exchange were reported in sheep, camels, and horses, which were better adapted to tropical conditions and deserts and were the means of transport along the ancient routes (Liu, 2010;Warmuth et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These potential incidences of gene flow were expecting in the closer regions of the tropics. Similar results were reported for goats of geographically close countries (Cañón et al, 2006;Al-Atiyat and Aljumaah, 2014). Considering different species, similar observations of reshaping genetic structure by genetic network exchange were reported in sheep, camels, and horses, which were better adapted to tropical conditions and deserts and were the means of transport along the ancient routes (Liu, 2010;Warmuth et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…In an agreement, Al-Atiyat and Aljumaah (2014) reported that 6.0% of total genetic variation was due to population variation of Ardi, Damascus, and Black Bedouin goats. The geographical partitioning study of goat diversity in Europe and the Middle East stated that 7% of the total genetic variation was explained by a difference between goat breeds (Cañón et al, 2006).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…They that the balance between oxidants and antioxidants may be impaired in neonatal animals. Aardi is an important local Saudi goats, with proven adaptation to arid environment [1]. Publications concerning the normal and abnormal levels of total as well as individual antioxidant profiles in Saudi breeds of ruminants are lacking.…”
Section: Introductionmentioning
confidence: 99%